2013
DOI: 10.1002/emmm.201303275
|View full text |Cite
|
Sign up to set email alerts
|

Compound loss of muscleblind‐like function in myotonic dystrophy

Abstract: Myotonic dystrophy (DM) is a multi-systemic disease that impacts cardiac and skeletal muscle as well as the central nervous system (CNS). DM is unusual because it is an RNA-mediated disorder due to the expression of toxic microsatellite expansion RNAs that alter the activities of RNA processing factors, including the muscleblind-like (MBNL) proteins. While these mutant RNAs inhibit MBNL1 splicing activity in heart and skeletal muscles, Mbnl1 knockout mice fail to recapitulate the full-range of DM symptoms in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
210
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(246 citation statements)
references
References 65 publications
27
210
3
Order By: Relevance
“…Consistent with this model, neonatal Mbnl compound knockout mice show characteristic manifestations of CDM, including frequent perinatal lethality, respiratory distress, reduced newborn body weight and postnatal growth, muscle histopathology, congenital spliceopathy, and gene expression abnormalities. These findings extend beyond our previous observations of muscle wasting in Mbnl muscle-specific double-knockout mice (Lee et al 2013) by demonstrating that muscle development is also severely compromised by compound loss of MBNL1 and MBNL2 activity. A central question is which of the hundreds of detectable RNA misprocessing events in CDM muscle truly contribute to abnormal muscle development.…”
Section: Mbnl Loss-of-function Models For Cdm Pathogenesissupporting
confidence: 84%
See 3 more Smart Citations
“…Consistent with this model, neonatal Mbnl compound knockout mice show characteristic manifestations of CDM, including frequent perinatal lethality, respiratory distress, reduced newborn body weight and postnatal growth, muscle histopathology, congenital spliceopathy, and gene expression abnormalities. These findings extend beyond our previous observations of muscle wasting in Mbnl muscle-specific double-knockout mice (Lee et al 2013) by demonstrating that muscle development is also severely compromised by compound loss of MBNL1 and MBNL2 activity. A central question is which of the hundreds of detectable RNA misprocessing events in CDM muscle truly contribute to abnormal muscle development.…”
Section: Mbnl Loss-of-function Models For Cdm Pathogenesissupporting
confidence: 84%
“…In agreement, dramatic neonatal lethality was observed in Mbnl1; Mbnl2 conditional double-knockout mice (Lee et al 2013), accompanied by a reduction in total body weight at birth (Fig. 3A,B).…”
Section: Congenital Myopathy and Spliceopathy In Mbnl1; Mbnl2 Double-supporting
confidence: 81%
See 2 more Smart Citations
“…Among them, MBNL1 was a major splicing factor with the highest motif fold enrichment. MBNL1 regulates alternative pre-mRNA splicing in many tissues and cell types, 23,35,[39][40][41][42] but its function in erythroid development was unclear. Our results demonstrated that both Mbnl1 exon 5 inclusion and exclusion isoforms were expressed during terminal erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%